2012
DOI: 10.1111/j.1742-6723.2012.01550.x
|View full text |Cite
|
Sign up to set email alerts
|

Senior Streaming Assessment Further Evaluation after Triage zone: A novel model of care encompassing various emergency department throughput measures

Abstract: Objective: Access block (AB) and hospital overcrowding adversely affect ED functionality. ED throughput measures have been described in the literature with positive impacts on key performance indicators (KPIs) – time to first seen, did‐not‐wait rates, off‐stretcher times for ambulances and ED length of stay figures. In this study, we aimed to assess the impact of a new model of care, the Senior Streaming Assessment Further Evaluation after Triage (SAFE‐T) zone concept on ED performance indicators and statistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 28 publications
1
53
0
1
Order By: Relevance
“…9,10 Recent studies have shown positive results based on early streaming decisions as part of a multi-pronged approach. 11 Similarly, past studies have also depicted the capabilities of different emergency services in predicting the need for hospital admission. [12][13][14][15] However, no studies to date have included early streaming by senior ED doctors at triage or soon after triage to predict a patient's disposition.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…9,10 Recent studies have shown positive results based on early streaming decisions as part of a multi-pronged approach. 11 Similarly, past studies have also depicted the capabilities of different emergency services in predicting the need for hospital admission. [12][13][14][15] However, no studies to date have included early streaming by senior ED doctors at triage or soon after triage to predict a patient's disposition.…”
Section: Introductionmentioning
confidence: 97%
“…1 Access block and ED overcrowding adversely affect ED functioning and the patient's length of stay (LOS) in ED. 11 Observation wards and short-stay units have added new streaming options for ED patients who require a short period of admission for clinical observation and intervention. 2 ED short-stay units have traditionally been reserved for patients who are most likely to be discharged within 24 h. Medical admission and assessment units have become commonplace in many hospitals as a conduit for medical admissions from the ED 3,4 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Five-level triage systems have been commonly used in emergency departments of countries where emergency medical services have been developed. [23][24][25][26][27][28] In the United States, ESI has emerged as a new triage system in which education and experience are needed; it is the most widely used and is the most valuable of emergency triage systems.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Inappropriate care areas and long durations for care in overcrowded emergency departments cause problems between patients and health care providers. [10][11][12][13][14] Different triage systems (2-Level, 3-Level, 4-Level and 5-Level) have been applied to determine the priority and management of health care for emergent patients in emergency departments.…”
mentioning
confidence: 99%
“…The rationale for restructuring is first and foremost to cope with an increased amount of patients while securing delivery of high quality and efficiency, concurrently with decreased overall hospital capacity 3 . Promotion of interdisciplinary teamwork and earlier senior physician involvement are examples of means to deliver timely and high quality treatment to patients within the EDs, which is essential for early diagnosis and provision of effective treatment of the increasing number of patients with co morbidities 4,5 . Other prevalent changes include introducing emergency medicine as a separate specialty 6 and formalized use of triage systems 7 .…”
Section: Review Of Literaturementioning
confidence: 99%